THE PROBLEM OF SOCIAL MATURITY IN PSYCHOLOGICAL RESEARCH - Master Nurmatov E. O. (Modern American Journals, 2025)
This article conductively analyzes the issue of social maturity which is one of the main issues of psychological research: the relationship and differences of social maturity with psychological maturity, the relationship between maturity and social maturity, the structural structure and characteristics of social maturity, the basic structural aspects of personality maturity.
Keywords: Social person, social maturity, psychological maturity, student personality, education, upbringing, self-concept, mental, volitional, emotional and physical maturity, self-awareness, social responsibility, behavior.